All digital sliding mode observer of a feedback-free interferometer for high dynamic range detection - Felão, Luiz H.V. [UNESP]; Martin, Roberta I. [UNESP]; Martinez, Guilherme A. [UNESP]; Sakamoto, João M.S.; Teixeira, Marcelo C.M. [UNESP]; Kitano, Cláudio [UNESP] (Optica Publishing Group, 2022)
A passive interferometry phase detection method is presented, which emulates the closed-loop high gain approach technique. This method comprises an all-digital closed-loop observer based on the variable structure and sliding modes nonlinear control theory, able to demodulate the phase of an open-loop feedback-free interferometer hardware. A proof-of-concept experiment is conducted by measuring complex displacements (module and angle) generated by a piezoelectric actuator. The results show that this method simplifies the optical hardware while providing features such as direct detection of the optical phase, increase of the dynamic range, high robustness, and dismissing of the feedback phase modulator and reset circuits.